Exploring the histories of health and deprivation in Britain, 1971–2011. (January 2020) - Dearden, Emily K.; Lloyd, Christopher D.; Green, Mark
Highlights: Considering lag effects of deprivation is important for explaining health variation. Results highlight the enduring effect of historical unemployment on health. Long-term socioeconomic history of local areas is salient for population health.